The Redevelopmental State: Governing Surplus Life and Land in the 'Urban Age'. Issue 3 (16th April 2018) - Doshi, Sapana
ABSTRACT: This article theorizes changing configurations of development governance emerging as states attempt to reconcile two contradictory pressures of global urbanization: dispossessing capitalist accumulation and demands for inclusive welfare. It introduces the 'redevelopmental state' as a dynamic spatio‐political framework for understanding how hegemonic rule is tenuously forged amid potentially volatile urban land struggles. Whereas Northern urban redevelopment theories are less attentive to post‐colonial urbanization processes and most developmental state scholarship has not focused on cities, the redevelopmental state offers an alternative conceptualization. It centres on how emerging regimes of territorial rule, development and political participation contour access to land and social benefits in Southern cities. Forged at key conjunctures of social pressure, these redevelopmental state spaces work through and beyond formal policies and institutions, and articulate with nationalist cultural politics of belonging and aspiration that foster consent for redevelopment while also legitimating exclusions, violence and dispossession. A case study of Mumbai illustrates redevelopmental state spaces that suture ethno‐religious nationalism, urbanized accumulation and populist welfare to unevenly distribute life capacities, garnering both cooperation and contestation. The article concludes by suggesting ways this spatially attuned framing can provide insights into the recent rise of ethno‐nationalism and authoritarian populism around the world.